2020
DOI: 10.3390/ijms21062216
|View full text |Cite
|
Sign up to set email alerts
|

Fli-1 Activation through Targeted Promoter Activity Regulation Using a Novel 3’, 5’-diprenylated Chalcone Inhibits Growth and Metastasis of Prostate Cancer Cells

Abstract: The friend leukemia integration 1 (Fli-1) gene is involved in the expression control of key genes in multiple pathogenic/physiological processes, including cell growth, differentiation, and apoptosis; this implies that Fli-1 is a strong candidate for drug development. In our previous study, a 3′,5′-diprenylated chalcone, (E)-1-(2-hydroxy-4-methoxy-3,5-diprenyl) phenyl-3-(3-pyridinyl)-propene-1-one (C10), was identified as a novel anti-prostate cancer (PCa) agent. Here, we investigated the molecular mechanisms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 46 publications
2
4
0
Order By: Relevance
“…To fully appreciate the relevance of FLI1 to CRC, its biological significance as an inhibitor to colorectal pathogenesis should also be considered. FLI1 as a specific target for anti‐cancer drugs can regulate the proliferation and apoptosis of cancer cells and block the formation of tumor blood vessels for controlling cancer cell invasion and migration 24 . Our functional experiments provided convincing evidence to support the correlation of FLI1 with an inhibited phenotype, in which FLI1 overexpression suppressed CRC cell colony formation, migration, and invasion, but promoted apoptosis.…”
Section: Discussionsupporting
confidence: 59%
“…To fully appreciate the relevance of FLI1 to CRC, its biological significance as an inhibitor to colorectal pathogenesis should also be considered. FLI1 as a specific target for anti‐cancer drugs can regulate the proliferation and apoptosis of cancer cells and block the formation of tumor blood vessels for controlling cancer cell invasion and migration 24 . Our functional experiments provided convincing evidence to support the correlation of FLI1 with an inhibited phenotype, in which FLI1 overexpression suppressed CRC cell colony formation, migration, and invasion, but promoted apoptosis.…”
Section: Discussionsupporting
confidence: 59%
“…Ma et al found that a 3′,5′-diprenylated chalcone ( 61 , Figure 14 ) likely showed friend leukemia integration-1 (Fli-1) agonism and regulation of the expression of VEGF-1, TGF-β2, intercellular cell adhesion molecule-1 (ICAM-1), p53, and MMP-1 genes, which are associated with tumor apoptosis, migration, and invasion in prostate cancer cells [ 163 ]. Iheagwam et al performed a molecular docking analysis, also showing that flavonoids ( 62 ) isolated from young Caesalpinia bonduc twigs and leaves displayed strong interactions with TK, VEGF, and MMP [ 164 ].…”
Section: Representative Mechanisms Of Anticancer Action Of Chalconesmentioning
confidence: 99%
“…VEGF receptor-2 (VEGFR-2) phosphorylates tyrosine at the Y658 and Y731 sites of VE-cadherin by inducing SRC family kinases, leading to destabilization of adherens junctions and increased endothelial cell permeability 28 , 29 . Youfen Ma et al found that the up-regulation of Fli-1 significantly inhibited VEGF expression 6 . In this experiment, both the LPS group and iri + LPS + apelin group showed similar results with low levels of Fli-1 with down-regulation of VE-cadherin, p-VE-cadherin, β-catenin and up-regulation of SRC, p-SRC, VEGF and VEGF-R.…”
Section: Discussionmentioning
confidence: 99%
“…Fli-1 is a transcription factor member of the ETS gene family, and it is mainly found in vascular endothelial cells, hematopoietic systems, immune cells and fibroblasts. A study found that Fli-1 regulates the expression of genes involved in the maintenance of vascular homeostasis, such as VEGF, platelet endothelial cell adhesion factor-1 (PECAM-1), VE-cadherin and S1P 6 , 7 . This suggests that the Fli-1 mediated endothelial cell homeostatic system plays an important regulatory role in vascular endothelial homeostasis, vascular skeleton formation and angiogenesis.…”
Section: Introductionmentioning
confidence: 99%